2019
DOI: 10.7759/cureus.4776
|View full text |Cite
|
Sign up to set email alerts
|

Compliance Rate of Surgical Antimicrobial Prophylaxis and its Association with Knowledge of Guidelines Among Surgical Residents in a Tertiary Care Public Hospital of a Developing Country

Abstract: Introduction Surgical antimicrobial prophylaxis (SAP) means the administration of antibiotics in surgical practice, and it reduces the likelihood of surgical site infections (SSIs). Inappropriate SAP practice regarding the prescription, timing, and duration of antibiotic use prolongs the hospital stay of patients, increases patient morbidity (by exposing them to the adverse effects of antibiotics), promotes bacterial resistance, and puts an economic burden on health care. While developed countries regularly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…However, screening and treatment of ASBU in diabetics has remained at the epicentre of a medical conundrum. Many long-term studies have established that routinely treating ASBU in all patients adversely affects patients' health (due to the associated side-effects of antibiotics) and promotes bacterial resistance, a major global medical challenge [ 12 , 14 - 15 ]. Thus, the current guidelines by the Infectious Diseases Society of America (IDSA) recommend against the screening and treatment of ASBU in diabetics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, screening and treatment of ASBU in diabetics has remained at the epicentre of a medical conundrum. Many long-term studies have established that routinely treating ASBU in all patients adversely affects patients' health (due to the associated side-effects of antibiotics) and promotes bacterial resistance, a major global medical challenge [ 12 , 14 - 15 ]. Thus, the current guidelines by the Infectious Diseases Society of America (IDSA) recommend against the screening and treatment of ASBU in diabetics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Despite this, studies have shown that optimal practice is not achieved in many hospitals, especially in developing countries. 12,13 The knowledge and attitudes of surgeons about appropriate SAP are important factors in the implementation of guidelines. It is necessary for hospital administrators and institutional quality-improvement departments to provide approaches to reduce such outcomes of antibiotic overuse as increased antibiotic resistance and higher financial costs to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing resistance of E.coli towards broad-spectrum antibiotics like nitrofurantoin is of great concern and demands the need for appropriate antibiotic use according to the recommended guidelines. As there is no strict adherence to antibiotic stewardship, the clinicians tend to prescribe broad-spectrum antibiotics that contribute to increased antimicrobial resistance [17,18]. Researchers have recommended conducting quality improvement programs to ensure appropriate antibiotic use according to the proposed guidelines, especially in a developing country like ours.…”
Section: Discussionmentioning
confidence: 99%